Eu me transmuto em outras: vozes múltiplas na canção de Itamar Assumpção - Barbosa, Bruno César Ribeiro (2019)
The aim of this research is to point out a possibility of reading the work of Itamar Assumpção, identifying, in his songs, an inventive and original compositional model, often used by the composer, in which the memory — individual or collective — through intertextual constructions, articulates constant dialogues with the tradition of Brazilian music and poetry. In this dialogue, the voices transmute into others, and in other utterances and texts, weaving a kind of mosaic, in which the parts that compose it join together and form a new object, although never homogeneous. From the attentive and responsive reading/listening of their discs — Beleléu, leléu, eu (1981); Às próprias custas S/A (1982); Sampa Midnight – Isso não vai ficar assim (1985); Intercontinental! Quem diria! Era só o que faltava!!! (1988); Bicho de 7 cabeças (1993); Ataulfo Alves por Itamar Assumpção – Pra sempre agora (1995); Pretobrás (1998, 2010) e Vasconcelos e Assumpção – Isso vai dar repercussão (2004) — a corpus with illustrative songs of its compositional model was developed, highlighting also the dialogue with the public listener and its trajectory through the music scene independent paulistana, in response to the consumerist model of the phonographic industry. The main theoretical references used as dialogue in this research are: Cavarero (2011); Zumthor (2010; 2014); Canclini (1998) and Tatit (2002; 2004; 2014).